2019
DOI: 10.31620/jccc.12.19/12
|View full text |Cite
|
Sign up to set email alerts
|

How Advertising Reflect Culture and Values: A Qualitative Analysis Study

Abstract: A successful advertising campaign is linked directly to how its perceived by different societies. This has led international companies to structure their advertising campaigns according to the culture of the society they are targeting. Hence, it is critical to have a strong understanding of the general attitude and characteristics of that particular society in order to create a message that resonates with the needs of its individuals .This study aims to identify the impact of advertising campaigns in stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It is clear that cultural values always exist in advertising. In a qualitative analysis study by Abokhoza et al (2019), which compared Pepsi's ads in Egypt and Pepsi's ads in Saudi Arabia, the findings showed that whether expressed explicitly or implicitly, most ad creators put cultural values first because advertising has both positive and negative influences on customers' life relying on the messages which reflect these values. This showed respect and preservation of their country's culture and helped introduce those spiritual values to other countries around the world.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that cultural values always exist in advertising. In a qualitative analysis study by Abokhoza et al (2019), which compared Pepsi's ads in Egypt and Pepsi's ads in Saudi Arabia, the findings showed that whether expressed explicitly or implicitly, most ad creators put cultural values first because advertising has both positive and negative influences on customers' life relying on the messages which reflect these values. This showed respect and preservation of their country's culture and helped introduce those spiritual values to other countries around the world.…”
Section: Introductionmentioning
confidence: 99%